Ecology and management of riparian zone vegetation along small coldwater streams in Northwestern Ontario - Lamb, Eric G. (2002)
This thesis synthesizes three papers on the ecology of the riparian zone vegetation found along small coldwater streams in northwestern Ontario. The objectives of this thesis were 1 ) to describe the biodiversity and distribution and abundance o f riparian zone plant species and vegetation types along the longitudinal and lateral gradients, 2) to evaluate the current buffer zone guidelines by comparing the riparian plant community between undisturbed sites and sites with adjacent clearcuts and forest fire, and 3) to examine the changes in the plant community trait structure found over the riparian-upland ecotone. 1 ) The riparian zones of these streams are diverse, with a large proportion o f the regional flora, including some locally rare species, represented. The vegetation is predominantly either an Alnus incana-dominated swamp thicket or a Calamagrostis canadensis and Carex aquatilis-dominated meadow marsh. Variation along the longitudinal gradient is weak with few species distributions significantly related to watershed size. Meadow marsh vegetation, however, is concentrated in watersheds 1000ha in area and smaller, likely due to the preference of beaver for streams of those sizes for dam construction. The riparian vegetation is remarkably homogenous along the lateral gradient. There are no distinct vegetation bands within the riparian zone, though some riparian-specialist species are more abundant near the streambank and some upland species are more common near the riparian-upland ecotone. The shoreward extent of the riparian zone, the riparian-upland ecotone, is marked by a strong shift in species composition at the limit of flooding and saturated soils. 2) Riparian plant community composition was compared between sites that were undisturbed, sites where clear-cuts were separated from the riparian zone by a buffer of upland forest, and sites where a forest fire had burned to the riparian zone-upland ecotone. No significant differences in the overall abundance and distribution of species in the riparian vegetation were found between the three disturbance classes, though a small number of species appeared to increase in abundance at burn sites. These results demonstrate that disturbances in the upland forest do not seriously impact the riparian zone plant community, likely because the riparian species are adapted to a high-light environment and flooding disturbance. The environmental factors that increase in the riparian zone following removal of the adjacent canopy, including light levels, temperature, and wind penetration, do not appear to have a significant influence on the riparian zone vegetation. These results suggest that aspects o f the current riparian management guidelines in northwestern Ontario may need to be re-evaluated. 3) The changes in importance of a range of reproductive, physiological, and morphological plant traits were examined over the riparian-upland ecotone. Traits with especially striking changes over the ecotone included leaf type, pollination and dispersal vector, clonal growth form, and a persistent seed bank. These trait patterns were used to generate hypotheses of potential functional explanations for the changes in plant community structure across the ecotone. These results have significance for ecotone theory as they demonstrate that plant traits can have very similar patterns of change across ecotones to those observed for the abundance of many species. Relationships between traits that represent potential functional relationships or tradeoffs are identified. Finally, this analysis has some implications for the types of traits that should be included in further trait-matrix studies.